Validation and measurement invariance of the Chinese version of the academic self-efficacy scale for university students - Zhao,Mengyuan; Kuan,Garry; Chau,Vinh Huy; Kueh,Yee Cheng (PeerJ, 2024)
Objectives The objective of this study was to examine the psychometric properties of the Chinese version of the Academic Self-Efficacy Scale (ASES-C) and confirm its measurement invariance across gender identities. Methods In this study, 502 university students (29.68% male, 70.32% female) with a mean age of 19.93 years (SD = 1.64) voluntarily participated. The Academic Self-Efficacy Scale (ASE) was utilized as a unidimensional measure of students’ learning efficacy. The English version of ASES was translated into Chinese using a forward-backward translation procedure. Confirmatory factor analysis (CFA) and invariance testing were conducted with the single-factor model of ASES. Composite reliability (CR) and internal consistency were calculated based on Cronbach’s alpha. Results Upon re-specification of the model, CFA results for the hypothesized single-factor model with eight items indicated an acceptable fit (CFI = 0.959, TLI = 0.943, SRMR = 0.036, RMSEA = 0.065). Cronbach’s alpha and CR values were 0.785 and 0.880, respectively. Multi-group CFA results demonstrated measurement equivalence for the Chinese version of ASES across gender identities. The findings supported the measurement invariance of ASES-C for both male and female participants. Conclusion The ASES-C, consisting of one factor and eight items, is a reliable instrument for assessing Chinese university students’ self-efficacy in learning. Furthermore, it is suitable for making meaningful comparisons across gender identities.
Keywords: Academic self-efficacy; Confirmatory factor analysis; Validation; Measurement invariance; University students